Pemahaman Tentang Sistem Pencernaan Manusia dan Hewan Siswa SDN Sukabumi 6 Probolinggo - ., Ani Anjarwati; ., Errina Dinda Festawanti; ., Yuni Wulandari; ., Faradella Rahmadhini; ., Muthmainnah (CV. ITTC INDONESIA, 2022)
The digestive system is a working system of organs that converts food from the mouth to the anus into the energy needed by the body. The digestive system consists of the mouth, esophagus, stomach, small intestine, large intestine and anus. The entire digestive system is in the form of a long, hollow, twisting and turning tube, called the alimentary canal, which starts at the oral cavity and ends at the anus.